Fraud dan Mahasiswa - Sigit Handoyo; Ridho Dwitama (Jurnal Aplikasi Bisnis, 2017)
Fraud commited by fraudster is aimed to take another one's or organization's assets illegally intended to take some benefit of them. This research aims to test the level of fraud commited by University student. Samples of this research are the accounting department students studying at Universitas Islam Indonesia experienced or involved or being involved in an organization both/either in internally at Universitas islam Indonesia and/or externally. Samples were takenby spreading of questionaires filled up by .214 students using purpossive, sampling method. Analysis applied of this reseacrh is descriptive qualitative with fraud triagle as a basic tool to analyse which are comprised 3 push or pull factors which are perceive, pressures, perceive opportunities, andperceived rasionalisation. The fundings of this research reveal that most of them experienced to commitfraud. They admit that the biggest pressure to commit fraud is the need of additional money for living costs. From perceivedopportunities factor, most of them said that the weakness of internal control is the prime pullfactor to commit fraud. Whitest the reality that most of their friends commit fraud is main reason or rasionalisation for them